A Study of the Different Properties and Characterization of Selenium for Photo-Voltaic Application with Variable: Investigating Selenium's Properties for Photo-Voltaic Application (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nikola Tesla said, “If you want to know the secrets of the universe, then think in terms of frequency and vibration.” When we talk about the photo-illumination of selenium element, the aforementioned principle greatly expounds the high electrical conductivity of the element, thus making it useful in photo-voltaic applications such as solar cars.